2006
DOI: 10.1002/cncr.21702
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection is associated with the development of hepatocellular carcinoma in chronic hepatitis C patients

Abstract: BACKGROUNDOccult hepatitis B virus (HBV) infection frequently occurs in patients with HBV surface antigen (HBsAg)‐negative chronic liver disease, and much evidence suggests that it is a risk factor for hepatocellular carcinoma (HCC) development. However, to the authors' knowledge, no follow‐up study has been performed to date evaluating HCC occurrence over time in chronic hepatitis patients with or without occult HBV infection.METHODSA cohort of the 380 HBsAg‐negative chronic hepatitis patients attending the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(158 citation statements)
references
References 27 publications
4
150
1
3
Order By: Relevance
“…Although the interaction between occult HBV and HCV infection could not be assessed properly, the study showed that the OR for HCC was about threefold higher for dual occult HBV and HCV infection compared to HCV infection alone, which is in line with the 2.9 OR for occult HBV infection for having HCC (cases) compared to having chronic hepatitis or cirrhosis (controls) among HCV RNA-positive subjects in a multicentre Italian study (Pollicino et al, 2004). In the Messina study (Squadrito et al, 2006), a strong interaction was evident between occult HBV infection and HCV infection: among 124 patients with HCV chronic hepatitis, seven of the 50 with concurrent occult HBV and HCV infection developed HCC (incidence rate: 2.18/100 person-years) compared to one of the 74 without occult HCV infection (incidence rate: 0.19/100 person-years).…”
Section: Occult Hepatitis B Virus Infectionmentioning
confidence: 55%
See 2 more Smart Citations
“…Although the interaction between occult HBV and HCV infection could not be assessed properly, the study showed that the OR for HCC was about threefold higher for dual occult HBV and HCV infection compared to HCV infection alone, which is in line with the 2.9 OR for occult HBV infection for having HCC (cases) compared to having chronic hepatitis or cirrhosis (controls) among HCV RNA-positive subjects in a multicentre Italian study (Pollicino et al, 2004). In the Messina study (Squadrito et al, 2006), a strong interaction was evident between occult HBV infection and HCV infection: among 124 patients with HCV chronic hepatitis, seven of the 50 with concurrent occult HBV and HCV infection developed HCC (incidence rate: 2.18/100 person-years) compared to one of the 74 without occult HCV infection (incidence rate: 0.19/100 person-years).…”
Section: Occult Hepatitis B Virus Infectionmentioning
confidence: 55%
“…In addition, other studies found a high proportion of occult HBV infections among HCV-positive HCC cases (Brechot et al, 2001) and that, in subjects with chronic HCV hepatitis, cirrhosis was more common among those with than those without occult HBV infection (Cacciola et al, 1999). In the Messina study, eight of nine HCC cases which developed in subjects with HCV-related chronic hepatitis were co-infected with occult HBV (Squadrito et al, 2006). In the Brescia HCC study, 37.4% of the HCV RNApositive and HBsAg-negative cases with HCC had HBV DNA in their sera, and 42.4% had a history of heavy alcohol intake, leaving a minority of HCC cases with HCV infection alone.…”
Section: Cirrhosis and Hepatocellular Carcinoma F Donato Et Almentioning
confidence: 88%
See 1 more Smart Citation
“…27,28 In addition, a cohort study also found that, among HBsAg-negative patients, HCC mostly developed in carriers of occult HBV. 29 One limitation of this study was the absence of HBV DNA assays for liver tissue. Most studies of occult HBV infection have reported higher HBV DNA detection rates in liver or peripheral blood mononuclear cells than in serum or plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies indicate an increased frequency of cirrhosis in occult HBVinfected patients, particularly if HCV co-infected (Torbenson and Thomas, 2002). Cryptic HBV infection is an important risk factor for the development of the HCC in patients with HCV-related cirrhosis (Pollicino et al, 2004;Squadrito et al, 2006). As occult HBV may persist in the infected livers both in integrated and episomal forms (Pollicino et al, 2004), it may contribute to hepatocellular transformation through the same mechanisms traditionally considered the basis of the tumorigenic properties of the HBV, including the capacity of the integrated virus to rearrange the host genome and the potential pro-oncogenic activity of the X protein that shares many molecular targets with HCV core and NS5A, including the ERK kinases, the b-catenin pathway, NF-kB and p53.…”
Section: Occult Hbv Infectionmentioning
confidence: 99%